British Andrology Society guidelines for the assessment of post vasectomy semen samples (2002). Issue 11 (1st November 2002) - Hancock, P; McLaughlin, E
Abstract : The British Andrology Society guidelines for the assessment of post vasectomy semen samples recommend that initial assessment is undertaken 16 weeks post vasectomy and after the patient has produced at least 24 ejaculates. The laboratory should examine a freshly produced seminal fluid specimen by direct microscopy and if no sperm are seen the centrifugate should be examined for the presence of motile and non-motile spermatozoa. It is recommended that the clinician should give clearance after the production of two consecutive sperm free ejaculates. In cases of persistent identification of non-motile spermatozoa the referring clinician should advise the patient regarding the cessation of other contraceptive precautions. Surgeons are responsible both preoperatively and postoperatively for the counselling of couples regarding complications and the possibility of late recanalisation after clearance.